UNDERSTANDING OF SCIENCE, TECHNOLOGY, ENGINEERING, ART, AND MATHEMATICS (STEAM) IN PGSD STUDENTS OF PGRI UNIVERSITY SEMARANG - Nuvitalia, Duwi; Saptaningrum, Ernawati; Baedhowi, Sunan (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
This study aims to describe the understanding of Primary School Teacher Education (PGSD) students regarding Science, Technology, Engineering, Art, and Mathematics (STEAM) learning. The research data were collected from PGSD students at Universitas PGRI Semarang using questionnaires and interviews. A total of 50 students enrolled in the Environmental Education course participated as respondents in this study. The students were given questionnaires and interviewed to obtain data on their understanding of STEAM. The results showed that the understanding of STEAM among PGSD students at Universitas PGRI Semarang could be categorized into five levels: very good understanding (SM), good understanding (M), fair understanding (CM), poor understanding (TM), and very poor understanding (STM). The findings revealed that 46% of students demonstrated a very good understanding of STEAM, 26% had a good understanding, 24% had a fair understanding, 2% had a poor understanding, and 2% had a very poor understanding of STEAM.